Crises and inequality: lessons from the global food, fuel, financial and economic crises of 2008–10 - Mendoza, Ronald U (Archīum Ateneo, 2011)
This article points to three main lessons for social policy from the global crises of 2008–10. First, there is evidence that the crises and their public finance ramifications could be characterized as ‘anti‐poor’. Second, even as the recovery begins to benefit the banking and financial sectors where the financial crisis began, it may also tend to further marginalize the poor, who are likely at their weakest and most vulnerable point, having undertaken a variety of coping strategies that are difficult to reverse quickly (e.g. drawing down on assets and possibly selling productive ones, taking on more debt, pulling children out of school). Third, if the crisis harms the poor and the ensuing recovery excludes them, then this could exacerbate inequity in human development. To prevent this, there is a need for pro‐poor countercyclical fiscal policies, boosting social spending and investments, as well as building on and adequately financing social protection systems, not just for poverty reduction but also to boost resilience against future crises.